2017
DOI: 10.1038/jes.2017.23
|View full text |Cite
|
Sign up to set email alerts
|

Child environmental exposures to water and sand at the beach: Findings from studies of over 68,000 subjects at 12 beaches

Abstract: Swimming and recreating in lakes, oceans, and rivers is common, yet the literature suggests children may be at greater risk of illness following such exposures. These effects might be due to differences in immunity or differing behavioral factors such as poorer hygiene, longer exposures to, and greater ingestion of potentially contaminated water and sand. We pooled data from 12 prospective cohorts (n=68,685) to examine exposures to potentially contaminated media such as beach water and sand, among children com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…A number of studies have found illnesses following beach swimming and linked to presence of indicator bacteria levels, where symptoms include diarrhea and rashes for example [28,29], although sometimes the association was limited or not found [30,31]. Deflorio-Barker et al [32] examined 12 studies to estimate the ingestion of water, sand, or algae and potential relationship to gastrointestinal illnesses. Young children aged 4–12 swallowed a greater amount of water for example compared to other age groups, increasing their potential exposures [32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have found illnesses following beach swimming and linked to presence of indicator bacteria levels, where symptoms include diarrhea and rashes for example [28,29], although sometimes the association was limited or not found [30,31]. Deflorio-Barker et al [32] examined 12 studies to estimate the ingestion of water, sand, or algae and potential relationship to gastrointestinal illnesses. Young children aged 4–12 swallowed a greater amount of water for example compared to other age groups, increasing their potential exposures [32].…”
Section: Resultsmentioning
confidence: 99%
“…Deflorio-Barker et al [32] examined 12 studies to estimate the ingestion of water, sand, or algae and potential relationship to gastrointestinal illnesses. Young children aged 4–12 swallowed a greater amount of water for example compared to other age groups, increasing their potential exposures [32].…”
Section: Resultsmentioning
confidence: 99%
“…This comparative analysis shows that the estimated cancer risks are sensitive to population-specific factors, particularly for exposure frequency. The study of children’s environmental health is often focused on assessing health consequences associated with inhalation exposure in outdoor environments, where children engage in physical activity [ 46 ]. However, the combination of crawling, non-dietary ingestion, and potential contamination of beach sand broaden the scope of potential health risks to children playing on a beach [ 21 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiological investigation showed that most of the patients were children. It has been demonstrated that, while swimming, compared to adults, children spend more time in the water and ingest a larger volume of water, thus increasing their exposure [ 26 , 27 ] and resulting in a higher infection risk and attributable disease burden [ 28 ]. High exposure of children in combination with the low infectious dose of NoV [ 2 ] and the incompletely developed immune system in young children explain the high number of affected children.…”
Section: Discussionmentioning
confidence: 99%